(untitled) (Global Journal of Management and Business Research, 2019)
The cause of congestions of traffic flow is its oversaturation with private cars. The fraction of private cars within traffic flow exceeds 80% [1]. Another reason is the low utilization of private vehicles. In Moscow, according to statistic, the average number of passengers in a car during rush hours is about 1.5 [1]. In this situation, the possibilities of public transport look very attractive. Vukan R. Vuchic, the wellknown American scientist, underlines that city governments recognize urban public transport as the critical element in achieving a balanced transportation system. In this case, #x201C;the support for urban transit provided by federal/national and other levels of government have played a major role in its upgrading through research and development, financing of a new system, new modes, and applied research for solving technical, operational and planning problems#x201D; [8].